Shedding Light on Metals Release from ChestnutWood toWine Spirit Using ICP-MS - Catarino, Sofia (2022)
Possible effects caused by mineral elements during wine spirit ageing are diverse. In this study, the evolution of the mineral composition of wine spirit during ageing with chestnut (Castanea sativa Mill.) wood was investigated. A wine distillate was aged in 250 L wooden barrels (traditional ageing) and in 50 L glass demijohns with wood staves and micro-oxygenation (alternative ageing). Sampling was performed after 21, 60, 180, 270, and 365 days of ageing. The elemental composition of the wine spirits, including alkaline, alkaline earth metals, and heavy metals, was assessed by quadrupole inductively coupled plasma mass spectrometry (Q-ICP-MS). For most of the elements, no significant differences between wine spirits from distinct ageing modalities were observed. Ageing time had significant effect on most of them, with different trends and distinct magnitude of changes, depending on each specific element. The concentrations of the mineral elements found in the wine spirits were very low, especially those of heavy metals, which is quite positive in terms of quality and food safety. Novel information on metals released from chestnut wood to wine spirits confirms its appropriateness for ageing this beverage